Quality and Safety Risk Assessment of Prefabricated Construction - Tian Li, Huijie Shang (Forest Chemicals Review, 2021)
This paper identifies the construction safety risk of prefabricated housing project. This paper uses the questionnaire data combined with TOPSIS method to obtain the attribute weight corresponding to each risk index and the square sum of the distance between positive ideal value and negative ideal value, which is used as the standard for ranking the advantages and disadvantages of risk indicators. Combined with entropy theory, this paper sorts and screens the risk factors, and constructs the risk index evaluation system. This paper analyzes the rationality of reliability and validity of the questionnaire to ensure the reliability of the questionnaire. In this paper, Bayesian network method is used to analyze the construction safety risk factors of prefabricated housing project. This paper uses the combination of risk matrix method and analytic hierarchy process (AHP) to evaluate the overall risk, get the risk level, and weigh whether to deal with the risk in combination with the risk acceptance principle. On this basis, this paper puts forward specific measures to deal with the construction safety risk of prefabricated housing project.